The new kingdom - Smith, Wilbur A; Chadbourn, Mark (Smith, Wilbur A. Ancient Egypt series., 2021)
Cast out of Lahun, Hui, once the ruler-in-waiting of the great city, seeks vengeance for the death of his father, swearing his allegiance to the enemies of Egypt and learning the art of war to fight to become the master of a new kingdom.